2008
DOI: 10.1182/blood-2007-07-101576
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations of JAK2 exon 12 in patients with JAK2 (V617F)-negative myeloproliferative disorders

Abstract: We searched for JAK2 exon 12 mutations in patients with JAK2 (V617F)-negative myeloproliferative disorders. Seventeen patients with polycythemia vera (PV), including 15 sporadic cases and 2 familial cases, carried deletions or duplications of exon 12 in circulating granulocytes but not in T lymphocytes. Two of the 8 mutations detected were novel, and the most frequent ones were N542-E543del and E543-D544del. Most patients with PV carrying an exon 12 mutation had isolated erythrocytosis at clinical onset, unlik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
217
1
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(243 citation statements)
references
References 24 publications
17
217
1
6
Order By: Relevance
“…47,48 • JAK2 exon 12 mutations are rare in ET or PMF, and their occurrence in PV is almost always associated with the absence of JAK2V617F and the presence of a subnormal serum erythropoietin level. 46,49 • The incidence of MPL mutations in MPN are too low (see above) to warrant their routine use in MPN diagnosis, except for clarification of equivocal morphology in the diagnosis of ET or PMF. 7 • JAK2 and MPL mutations do not occur in healthy subjects or in those with non-clonal causes of myeloproliferation.…”
Section: Jak2 and Mpl Mutation Screening In Routine Clinical Practicementioning
confidence: 99%
“…47,48 • JAK2 exon 12 mutations are rare in ET or PMF, and their occurrence in PV is almost always associated with the absence of JAK2V617F and the presence of a subnormal serum erythropoietin level. 46,49 • The incidence of MPL mutations in MPN are too low (see above) to warrant their routine use in MPN diagnosis, except for clarification of equivocal morphology in the diagnosis of ET or PMF. 7 • JAK2 and MPL mutations do not occur in healthy subjects or in those with non-clonal causes of myeloproliferation.…”
Section: Jak2 and Mpl Mutation Screening In Routine Clinical Practicementioning
confidence: 99%
“…However, the V617F mutation renders the JAK2 protein constitutively active in the absence of a corresponding stimulus. Mutations in other parts of the gene, including exon 12, have also been observed in a sub group of MPN patients [8,9]. The identification of such a frequently mutated gene prompted further investiga tion into its role in the development of the disease.…”
Section: Mutations Affecting the Jak-stat Signaling Pathwaymentioning
confidence: 99%
“…The most frequently mutated amino-acid sequences span from 542 to 544. 17,112 In vitro studies demonstrated that JAK2 exon 12 mutations activate multiple pathways that are associated with erythropoietin signaling. More importantly, one mutation studied in detail resulted in the development of a myeloproliferative phenotype in a mouse model.…”
Section: Jak2 Mutationsmentioning
confidence: 99%
“…Patients with JAK2 exon 12 mutations typically present with a myeloproliferative syndrome accompanied by isolated erythrocytosis with suppressed erythropoietin production. 17,112 In addition, base-pair substitutions or deletions within the JH2 domain were identified not only in MPD but also in rare cases of acute leukemias and lymphoid disorders as summarized in Table 3.…”
Section: Jak2 Mutationsmentioning
confidence: 99%